The Relationship of Hypertension with Death in Covid-19 Patients Treated at Tugurejo Hospital Semarang - Nanindya Ailsa Pramudhita; Setyoko Setyoko; Susilo Budi Pratama (CV. Publikasi Indonesia, 2024)
Covid-19 is a disease caused by SARS-CoV-2. Hypertension is a comorbidity that can be experienced by COVID-19 patients and is associated with an increased risk of severity and death. The purpose of this study is to look at the relationship between hypertension and death in COVID-19 patients treated at Tugurejo Hospital Semarang. This study is a quantitative study that uses an analytical observational design and a cross-sectional approach. The sampling technique was purposive sampling (judgment sampling) on 84 COVID-19 patients treated at Tugurejo Hospital Semarang for the May-November 2021 period. Data were obtained from medical records and analyzed univariately and bivariately with the Chi-Square test. Most patients were aged ≥50 years (40.5%), male (53.6%), high school educated (51.2%), employed as private employees (42.9%), suffered from hypertension (53.6%) and did not experience death (51.2%). The Chi-Square test resulted in a significant association between hypertension and death of COVID-19 patients (p = 0.031). There is an essential relationship between hypertension and death in COVID-19 patients at Tugurejo Hospital Semarang.